Records Committee review for rare bird sighting of Lesser Black-backed at Red Rock Lake, 1994 - Armstrong, Eugeneet al (1994)
Records Committee review for a Lesser Black-backed Gull at Red Rock Lake in Marion County, IA on October 29, 1994. Includes a record review document with votes and a documentation form submitted to the committee. Epson - sheet feed